Burkholderia from Fungus Gardens of Fungus-Growing Ants Produces Antifungals That Inhibit the Specialized Parasite Escovopsis - Francoeur, Charlotte B. (2021)
Within animal-associated microbiomes, the functional roles of specific microbial taxa are often uncharacterized. Here, we use the fungus-growing ant system, a model for microbial symbiosis, to determine the potential defensive roles of key bacterial taxa present in the ants’ fungus gardens. Fungus gardens serve as an external digestive system for the ants, with mutualistic fungi in the genus Leucoagaricus converting the plant substrate into energy for the ants. The fungus garden is host to specialized parasitic fungi in the genus Escovopsis. Here, we examine the potential role of Burkholderia spp. that occur within ant fungus gardens in inhibiting Escovopsis. We isolated members of the bacterial genera Burkholderia and Paraburkholderia from 50% of the 52 colonies sampled, indicating that members of the family Burkholderiaceae are common inhabitants in the fungus gardens of a diverse range of fungus-growing ant genera. Using antimicrobial inhibition bioassays, we found that 28 out of 32 isolates inhibited at least one Escovopsis strain with a zone of inhibition greater than 1cm. Genomic assessment of fungus garden-associated Burkholderiaceae indicated that isolates with strong inhibition all belonged to the genus Burkholderia and contained biosynthetic gene clusters that encoded the production of two antifungals: burkholdine1213 and pyrrolnitrin. Organic extracts of cultured isolates confirmed that these compounds are responsible for antifungal activities that inhibit Escovopsis but, at equivalent concentrations, not Leucoagaricus spp. Overall, these new findings, combined with previous evidence, suggest that members of the fungus garden microbiome play an important role in maintaining the health and function of fungus-growing ant colonies.